Pricing and choice of project finance bonds - Guedes, Sebastião Maria Couceiro da Costa Sousa (2021)
This dissertation examines the pricing of project finance (PF) vis-à-vis corporate finance (CF) bonds and studies the factors that influence the sponsors’/issuers’ choice between off-balance sheet PF bonds and on-balance sheet CF bonds. Using a cross-section sample of 763 PF and 46,433 similar CF bonds globally issued between January 1993 and January 2020, we compare credit spreads and pricing factors of the both bond types and analyse their pricing determinants. Findings suggest that, although credit ratings are the most important pricing determinants for both PF and CF bonds at issuance, investors also rely on borrowers’ characteristics as well as on contractual and macroeconomic factors beyond these ratings. The results show that credit spreads for PF and CF bonds are influenced differently by common pricing characteristics. Additionally, we find that PF bonds have, on average, 30.85 bps higher credit spreads than CF bonds. This difference decreases to 19.15 bps when we include sponsors’/issuers’ characteristics in the pricing analysis. Publicly traded firms that prefer PF to CF are smaller, less profitable, less creditworthy and have lower asset tangibility. Finally, our results also document that issuers use PF to raise relatively larger amounts of debt and seek long-term funding.